Obesity and post-operative cognitive dysfunction: a systematic review and meta-analysis - Feinkohl, Insa; Winterer, Georg; Pischon, Tobias (Diabetes/metabolism research and reviews, 2016)
Background Post‐operative cognitive dysfunction, a condition distinct from post‐operative delirium (POD), occurs frequently after surgery, and is related to dementia and premature death. Obesity increases the risk of late‐life cognitive impairment, but little is known about its role in post‐operative cognitive dysfunction. We conducted a systematic review and meta‐analysis of studies on the association between obesity and risk of post‐operative cognitive dysfunction. Methods PubMed and the Cochrane Library were systematically searched. Studies were included if they had prospective designs, reported on human adults undergoing surgery, if cognitive function was measured pre‐ and post‐surgery, if obesity, body mass index (BMI) and/or body weight were ascertained, and if associations with post‐operative cognitive dysfunction were reported as relative risks or odds ratios. Underweight, weight loss, and post‐operative delirium were not considered. Results Inclusion criteria were met by six articles. Samples totaled 1432 older patients (mean age ≥62 years) who were followed up for 24 h to 12 months after surgery. Analysis of studies with obesity defined as a categorical measure found a non‐significantly higher risk of post‐operative cognitive dysfunction among persons with BMI > 30 kg/m2 versus ≤30 kg/m2 (relative risk 1.27; 95% confidence interval 0.95, 1.70; p = 0.10). No such associations were found for studies that analysed BMI or body weight continuously as predictors of post‐operative cognitive dysfunction (relative risk 0.98 per kg/m2; 95% confidence interval 0.93, 1.03, p = 0.45; relative risk 0.99 per kg; 95% confidence interval 0.89, 1.09; p = 0.83, respectively). Conclusions Few studies have addressed the topic, and the results of these studies provide only limited support for an increased risk of post‐operative cognitive dysfunction in patients who are obese. Further large‐scale, prospective investigations are necessary for clarification. Copyright © 2016 John Wiley & Sons, Ltd.